ANALYSIS OF STUDENT RESPONSES TO THE IMPLEMENTATION OF THE DISCOVERY LEARNING MODEL BASED ON STEM CLASS VIII SMP N 13 PADANG - Wasni Fitri; Arief Muttaqiin (Universe, 2020)
ABSTRACT This study aims to determine student responses to learning by implementation STEM-based Discovery Learning in class VIII.6 SMP N 13 Padang. This research was conducted by giving a questionnaire responses as many as 25 statements consisting of three indicators namely interest and learning benefits, critical thinking skills, and student activities, and given to 30 students. The data obtained is based on the answers obtained from the questionnaire and analyzed using a Likert Scale. From the results of the study that learning with STEM-based Discovery Learning is good for teaching human respiratory system material and also giving positive responses from students.